Endophytic Pestalotiopsis species associated with Rhododendron in Cangshan Mountain, Yunnan Province, China - Gu, Rui; Bao, Dan-Feng; Shen, Hong-Wei; Su, Xi-Jun; Li, Yun-Xia; Luo, Zong-Long (Frontiers in Microbiology, 2022)
Rhododendron is an essential ornamental plant that is abundant in Yunnan province. In Cangshan Mountain, Yunnan, China, 61 species of Rhododendron have been reported. Endophytic fungi are internal plant tissue inhabitants that do not harm the host. It has emerged as an exciting research topic as they have the potential to provide numerous secondary metabolites. This study is focused on taxonomic novelties and new host records of endophytic fungi associated with Rhododendron plants collected from Cangshan Mountain in Yunnan Province, China. Pestalotiopsis fungi are associated with a vast array of plant species worldwide. In this study, fresh leaves of Rhododendron cyanocarpum, Rhododendron decorum, and Rhododendron delavayi were collected from Cangshan Mountain, Yunnan Province, China. Endophytic Pestalotiopsis fungi associated with Rhododendron were characterized based on phylogenetic analyses of combined ITS, TEF1-α, and TUB genes along with morphological characteristics. Six new species (Pestalotiopsis appendiculata, Pestalotiopsis cangshanensis, Pestalotiopsis daliensis, Pestalotiopsis fusoidea, Pestalotiopsis rosarioides, and Pestalotiopsis suae) and a new host record (Pestalotiopsis trachicarpicola) are described. Detailed descriptions and color photo plates of these species are provided. It is the first time that the endophytic fungi of Rhododendron plants in Cangshan Mountain have been studied.